2012
DOI: 10.1021/ie300534e
|View full text |Cite
|
Sign up to set email alerts
|

Anion Exchange Resins for the Selective Separation of Technetium from Uranium in Carbonate Solutions

Abstract: In alkaline carbonate solutions both technetium and uranium exist as anionic species, TcO 4 − and UO 2 (CO 3 ) 3 4− , which makes separating Tc and U from each other more challenging compared to acidic PUREX type solutions where uranium forms neutral or cationic complexes. We tested the batch separation of 99 Tc, 238 U, and 239 Pu from carbonate solutions using anion exchange resins with different properties, including Purolite A530E, Reillex HPQ, and Dowex Marathon WBA. Overall, the highest K d values for per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Commercially available polymeric anion-exchange resins show a notable advantage in 99 TcO 4 – uptake selectivity, but their poor radiation resistance impedes their practical applications in the radiological field especially in used fuel repossessing, where strong radiation fields (high fluxes of α, γ, β, and neutron irradiations) are present at extremely high dose rates. It was reported that the 99 TcO 4 – uptake capacity would gradually decrease as the receiving radiation doses increase 15f,17. This critical issue is further amplified given that the 99 TcO 4 – uptake kinetics by these materials are rather slow, leading to a significantly higher dosage received during the anion-exchange process.…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available polymeric anion-exchange resins show a notable advantage in 99 TcO 4 – uptake selectivity, but their poor radiation resistance impedes their practical applications in the radiological field especially in used fuel repossessing, where strong radiation fields (high fluxes of α, γ, β, and neutron irradiations) are present at extremely high dose rates. It was reported that the 99 TcO 4 – uptake capacity would gradually decrease as the receiving radiation doses increase 15f,17. This critical issue is further amplified given that the 99 TcO 4 – uptake kinetics by these materials are rather slow, leading to a significantly higher dosage received during the anion-exchange process.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Developing the chemistry of these MO 4 x-anions is also needed to support a variety of applications, which include use as stoichiometric and catalytic oxidants, 18 in radiopharmaceutical purifications, 19 and in advanced nuclear fuel separations. 20 Despite the similarities of these isoelectronic d 0 MO 4 2-and MO 4 1-anions, we find significant differences in σ-and π-type metal oxo orbital mixing both for adjacent metals in the same row as well as for metals within the same group triad.…”
Section: Introductionmentioning
confidence: 57%
“…Moreover, high positive charge density and hydrophobicity also increase the affinity of the 2D layers for 99 TcO 4 − anions. Note that SCU-103 exhibits very high anion-exchange efficiency in contrast to typical commercial resins (A532E and A530E) 16 , 18 and other anion exchangers designed for the removal of anionic contaminants including NDTB-1 13 , 14 , SLUG-21 39 , UiO-66-NH 3 + 48 , comparable to those of SCU-100 16 , SCU-101 42 , and SCU-102 45 . The ultrafast sorption kinetics has great application significance and unique advantages as the short contact time between sorbents and radioactive waste solution would effectively reduce the risk of nuclear leakage and lower the damage of sorbents induced by radiation and hydrolysis.…”
Section: Resultsmentioning
confidence: 95%
“…Purely inorganic anion-exchange materials also suffer from low capacity and a narrow applicable pH range 16 . Commercially available anion-exchange resins deliver high uptake selectivity towards 99 TcO 4 − 17 , 18 , however, poor radiation-resistance results in gradual decrease in uptake capacity with the increase of exposed radiation dosage during the anion-exchange process 19 . In addition, the sorption kinetics are rather slow and the elution is difficult owing to the strong affinity between resins and 99 TcO 4 − anion.…”
Section: Introductionmentioning
confidence: 99%